The Reality of The Electronic Management for Academic Administrators at The University of Tabuk - Albalawi, Marzouqah Hamoud (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the reality of the electronic management of the academic administrators of Tabuk University in Saudi Arabia. The study used descriptive analytical method by applying a questionnaire to a sample of (117) academic administrators at Tabuk University for the academic year 2014-2015. The study reached several results, the most important of which is that the reality of electronic administration at Tabuk University was average. In addition, the field of training policies in the application of electronic management came first place and then the field of electronic monitoring and evaluation, then the field of electronic implementation, planning and organization, and finally the field of performance evaluation. The study found that the level of the field of training policies in the application of electronic management was high because of the interest of the university administration to provide the latest software and equipment that develops administrative work. The study found that the level of planning and organization was between high and medium. The study recommended the need to train academic administrators on electronic management in the field of planning and organization, and work to raise the awareness of the senior management of the university and raise the awareness of academic administrators of the importance of electronic management and its effective role in administrative work. The study also recommended conducting training courses in electronic administration for deans of colleges. In addition to adopting the proposed program that was developed to develop the efficiency of academic administrators in electronic administration at Tabuk University.
Keywords: Reality; Electronic Administration; Development; Efficiency of Academic Administrators